The Influencing Factors of Nutrition and Diet Health Knowledge Dissemination Using the WeChat Official Account in Health Promotion - Bian, Dongsheng; Shi, Yongmei; Tang, Wenjia; Li, Dong; Han, Kangni; Shi, Chenshu; Li, Guohong; Zhu, Fan (Frontiers in Public Health, 2021)
Background: The promotion of a healthy diet via health education is a component of the “Healthy China 2030” plan. However, few studies have reported whether health knowledge about nutrition and diet has gained public attention, and whether it is needed by the public. Methods: The numbers of views, shares, and reads of articles published by the official WeChat account of a hospital in China were accessed. The influence index was obtained via the entropy analysis of these three indices. A questionnaire survey was developed based on the purpose of the study and the conclusion of the content analysis, which conducted to analyze users' requirements for health knowledge and their influencing factors. Moreover, risk factors were explored by logistic regression models. Results: Of the 103 articles considered in this study, four articles in the Top 10 were related to nutrition and diet. The influence index of nutrition and diet knowledge was found to be the highest in the content analysis (p < 0.05). The higher degrees of humor (β = 0.224, p = 0.027), nutrition and diet articles (β = 0.776, p = 0.034), and cover articles (β = 0.312, p = 0.021) have significant influences on the influence index. In total, 581 questionnaires were obtained, and 78.1% of the respondents reported believing that the health knowledge of greatest concern was that related to nutrition and diet. Multivariate logistic regression analyses were conducted to explore the associations between the features of the articles and users reading nutrition and diet knowledge; it was found that gender (female, OR: 4.651, 95%Cl: 2.598, 8.325, and p < 0.001), age (young adult, OR: 0.358, 95%Cl: 0.266, 0.481, and p < 0.001), cancer precaution knowledge (OR: 4.333, 95%Cl: 2.262, 8.299, and p < 0.001), traditional Chinese medicine (OR: 2.121, 95%Cl: 1.064, 4.230, and p = 0.033), the knowledge acquisition approach [circle of friends (OR: 2.586, 95%Cl: 1.373, 4.868, and p = 0.003), social media (OR: 2.183, 95%Cl: 1.204, 3.960, and p = 0.010)), hospitals (OR: 3.194, 95%Cl: 1.793, 5.692, and p < 0.001), television media (OR: 4.348, 95%Cl: 2.341, 8.077, and p < 0.001)], and social media strategies [professionalism and authority (OR: 2.354, 95%Cl: 1.231, 4.505, and p = 0.006)] have statistically significant relationships with users reading nutrition and diet knowledge. Conclusion: Nutrition and diet knowledge could contribute to WeChat user engagement of health information dissemination. Nutrition professionals should improve the scientific popularization ability and effectively use social media for health promotion.